ASME 2017 International Technical Conference and Exhibition on Packaging and Integration of Electronic and Photonic Microsystem 2017
DOI: 10.1115/ipack2017-74030
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Mini-Thermosyphon for Cooling of Datacenters: Experiments, Modeling and Simulations

Abstract: Nowadays, datacenters heat density dissipation follows an exponential increasing trend that is reaching the heat removal limits of the traditional air-cooling technology. Two-phase cooling implemented within a gravity-driven system represents a scalable and viable long-term solution for datacenter cooling in order to increase the heat density dissipation with larger energy efficiency and lower acoustic noise. The present article builds upon the 4-part set of papers presented at ITHERM 2016 for a 15-cm height t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The use of twophase cooling, rather than single-phase liquid-based cooling systems, is strongly motivated due to their reduced mass flowrates, lower pumping power, and smaller facility size [14], while providing higher heat transfer coefficients and more uniform temperature profiles [12]. Previous thermosyphon prototypes such as [15], however, had a very large footprint area (1m ⇥ 1m) making them impractical in commercial servers. Nonetheless, recent work by [16] and [8] led to the design of micro-scale thermosyphons which can be placed directly on top of a CPU.…”
Section: A Data Center Cooling Methodsmentioning
confidence: 99%
“…The use of twophase cooling, rather than single-phase liquid-based cooling systems, is strongly motivated due to their reduced mass flowrates, lower pumping power, and smaller facility size [14], while providing higher heat transfer coefficients and more uniform temperature profiles [12]. Previous thermosyphon prototypes such as [15], however, had a very large footprint area (1m ⇥ 1m) making them impractical in commercial servers. Nonetheless, recent work by [16] and [8] led to the design of micro-scale thermosyphons which can be placed directly on top of a CPU.…”
Section: A Data Center Cooling Methodsmentioning
confidence: 99%
“…The most recent thermosyphon built, which demonstrates comparable performance results to a pumped cooling loop system, has 15 cm height but a large footprint area of 1 m × 1 m [7], [8]. This mini-thermosyphon validates the two flow regimes: i) gravitational dominant regime, and ii) frictional dominant regime.…”
Section: State-of-the-art On Mini-thermosyphon Design and Manufacturingmentioning
confidence: 99%
“…This change of slope is characterized by the authors as a change in the flow pattern, possibly a transition from slug to annular flow. The model also had a change of slope, even though it appears that the predictability was not as accurate as for lower heat loads, perhaps pointing out that the model could be improved for different flow patterns.While contrasting the mass flow rate as a function of heat load, obtained by the model ofOng et al (2017) with their experimental data, it is evident that the model showed both gravitational and frictional dominant regimes across their whole heat load input range, as did the experimental campaign. However, the model was shown to overpredict the mass flow rate especially for lower heat fluxes (15 to 25 W/cm 2 ) which characterize the gravitational dominant regime.…”
mentioning
confidence: 83%
“…The study performed by Ong et al (2017) centered on adding data for a wider range of imposed heat load for a thermosyphon loop of 15 cm of height, designed to cool a pseudo-chip which emulated a server. The authors performed more experimental tests and provided new validations for the LTCM code on working fluid's mass flow rate, mean chip temperature, and system pressure.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation